Lipoprotein‐associated phospholipase A2 and cardiovascular disease risk in HIV infection. Issue 9 (20th March 2014) - Ross Eckard, A; Longenecker, CT; Jiang, Y; Debanne, SM; Labbato, D; Storer, N; McComsey, GA
<x xml:space="preserve">Abstract</x> Objectives HIV‐infected patients on antiretroviral therapy (ART) have an increased cardiovascular disease (CVD) risk as a result of heightened inflammation and immune activation, despite at times having normal lipids and few traditional risk factors. Biomarkers are needed to identify such patients before a clinical event. Lipoprotein‐associated phospholipase A2 (Lp‐PLA2) predicts CVD events in the general population. This study investigated the relationship between Lp‐PLA2 and markers of CVD risk, systemic inflammation, immune activation, and coagulation in HIV infection. Methods One hundred subjects on stable ART with normal fasting low‐density lipoprotein (LDL) cholesterol were enrolled in the study. Plasma Lp‐PLA2 concentrations were measured by enzyme‐linked immunosorbent assay (ELISA; > 200 ng/mL was considered high CVD risk). Subclinical atherosclerosis, endothelial function, inflammation, immune activation and fasting lipids were also evaluated. Results The median age of the patients was 47 years and 77% were male. Median (range) Lp‐PLA2 was 209 (71–402) ng/mL. Fifty‐seven per cent of patients had Lp‐PLA2 concentrations > 200 ng/mL. Lp‐PLA2 was positively correlated with soluble markers of inflammation or immune activation (tumour necrosis factor receptor‐II, intercellular and vascular cellular adhesion molecules, and CD14; all R = 0.3; P < 0.01), and negatively correlated with coagulation markers (D‐dimer and fibrinogen; both R = −0.2; P < 0.04). Lp‐PLA2 was not correlated with lipids, coronary artery calcium score, or flow‐mediated vasodilation, but trended towards a significant correlation with carotid intima‐media thickness (R = 0.2; P = 0.05). Conclusions In this population with stable ART and normal LDL cholesterol, Lp‐PLA2 was in the high CVD risk category in the majority of subjects. Lp‐PLA2 appears to be associated with inflammation/immune activation, but also with anti‐thrombotic effects. Lp‐PLA2 may represent a valuable early biomarker of CVD risk in HIV infection before subclinical atherosclerosis can be detected.